Impact of 21‐Gene Breast Cancer Assay on Treatment Decision for Patients with T1–T3, N0–N1, Estrogen Receptor‐Positive/Human Epidermal Growth Receptor 2‐Negative Breast Cancer: Final Results of the Prospective Multicenter ROXANE Study. (31st May 2019) - Dieci, Maria Vittoria; Guarneri, Valentina; Zustovich, Fable; Mion, Marta; Morandi, Paolo; Bria, Emilio; Merlini, Laura; Bullian, Pierluigi; Oliani, Cristina; Gori, Stefania; Giarratano, Tommaso; Orvieto, Enrico; et al.
Abstract: Background: The ROXANE Italian prospective study evaluated the impact of the 21‐gene Recurrence Score (RS) results on adjuvant treatment decision for patients with early breast cancer. Materials and Methods: Nine centers participated. Physicians used the RS test whenever unsure about adjuvant treatment recommendation for patients with estrogen receptor‐positive/human epidermal growth receptor 2‐negative, T1–T3, N0–N1 early breast cancer. Pre‐RS and post‐RS treatment recommendations were collected. Results: A total of 251 patients were included. N0 patients (61%) showed higher grade ( p < .001) and higher Ki67 ( p = .001) and were more frequently progesterone receptor negative ( p = .012) as compared with N1 patients. RS results were as follows: <11, n = 63 (25.1%); 11–25, n = 143 (57%); and ≥26, n = 45 (17.9%). Higher RS was found in N0 vs. N1 patients ( p = .001) and in cases of G3 ( p < .001) and higher Ki67 ( p < .001). The rate of change in treatment decision was 30% ( n = 75), mostly from chemotherapy (CT) plus hormone therapy (CT + HT) to hormone therapy (HT; 76%, n = 57/75). The proportion of patients recommended to CT + HT was significantly reduced from pre‐RS to post‐RS (52% to 36%, p < .0001). CT use reduction was more evident for N1 patients (55% to 27%) than for N0 patients (50% to 42%) and was observed only in cases of RS ≤17. Conclusion: Physicians predominantly used the 21‐gene assay in N0 patients with a more aggressive biology or in N1 patients showing more indolent biology. In this selected patient population, the use of RS testing led to a 30% rate of change in treatment decision. In the N1 patient subgroup, the use of RS testing contributed to reduce CT use by more than half. Implications for Practice: This study shows that, even in a context in which physicians recommend a high proportion of patients to endocrine treatment alone before knowing the results of the Recurrence Score (RS) assay, the use of the RS test, whenever uncertainty regarding adjuvant treatment recommendation is present, significantly contributes in further reducing the use of chemotherapy, especially for N1 patients. Abstract : Results of the ROXANE study, evaluating the effect of the 21‐gene recurrence score assay on adjuvant treatment decisions for patients with breast cancer, are reported.